MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDes) IN TOLADA VILLAGE, MALANGKE DISTRICT, NORTH LUWU REGENCY - Silvia, Indra; Guntur, Muhammad; Rukmana, Novayanti Sopia (Jurnal Aktor, 2025)
This study aims to find out how the Management of Village-Owned Enterprises in Tolada Village, Malangke District, North Luwu Regency. This research is motivated because Tolada Village is one of the villages that has a low level of community welfare to advance the welfare of the people of Tolada village, The Village Government established a village-owned enterprise in 2015 and began to run smoothly in 2018, in this study researchers used George R. Terry Theory (1990) with 4 indicators, namely: 1) Planning 2) Organizing 3) Actuating 4) Controlling. This type of research is qualitative research with data collection techniques, namely by observation, interview, and documentation. Data obtained from research results are processed using data analysis techniques, data reduction, data presentation and conclusions. The results of the study show how the management of Village-Owned Enterprises in Tolada Village, Malangke District, North Luwu Regency can be said to be good as seen from the indicators: 1) Planning, 2) Organizing, 3) Actuating, 4) Controlling. However, it needs to be improved on the indicators of Organizing (Organizing) and also supervision (Controlling) has not been done well